Clinical benefits of immune checkpoint inhibitors for malignant peripheral nerve sheath tumors with NF2 mutation: a case report - Jiang, Yale; Zhao, Guo; Tang, Qiyu; Xing, Shujun; Wang, Shuhang; Li, Ning (Frontiers in Immunology, 2025)
BackgroundMalignant peripheral nerve sheath tumors (MPNSTs), which arise from peripheral nerves or cells associated with nerve sheaths, are uncommon and biologically aggressive sarcomas. Currently, immune checkpoint inhibitors (ICIs) have exhibited antitumor efficiency in various sarcomas. However, there have been few reports on the clinical features and treatment response of ICIs in MPNSTs.Case presentationWe report a 22-year-old woman with an NF2 pathogenic mutation and typical manifestations of MPNST. Her symptoms improved after the administration of intravenous anti-PD-1 monoclonal antibody and it demonstrated a sustained clinical benefit for 19.7 months. A literature review of four cases was included to emphasize the efficiency of ICIs in the treatment of MPNSTs. Four cases reporting ICI treatment in MPNSTs were identified using Web of Science. All the previous cases that received ICIs had reported a complete response regardless of PD-L1 expression and genetic predisposition, indicating potential efficacy in this rare and intractable tumor. Our case showed the sustained clinical benefit of anti-PD-1 monoclonal antibody in the uncommon tumor subtype harboring an NF2 mutation as a first-line therapy after non-radical surgery despite the heavy tumor burden.ConclusionOur case indicated that ICIs are warranted as first-line monotherapy in MPNSTs given the possibility of life quality improvement and durable clinical benefit.